Students’ Perceptions of Dubbing Muted Animation in English Speaking Classrooms: A Case Study at Greenfield Language College (GRACE) - Ariani; Syarifuddin Dollah; Andi Anto Patak; Fitriani (International Journal of Language, Education, and Literature, 2025)
This paper aims to explore students' perceptions of using the dubbing muted animation movie clip technique in English speaking classrooms at Greenfield Language College. We employed a case study as our research design. By using convenient sampling, we recruited 5 participants to participate in our study. The results show that students at Greenfield Language College overwhelmingly perceive the dubbing muted animation movie clip technique in English speaking classrooms as a highly positive pedagogical approach, as evidenced by recurring themes of enjoyment and interest, increased speaking confidence, and a proactive engagement with challenges and difficulties. This study contributes to a more nuanced understanding of effective multimedia integration in language pedagogy and offers valuable insights for curriculum developers and educators.